2010
DOI: 10.1007/s10157-010-0356-2
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone pulse therapy combined with mizoribine following tonsillectomy for immunoglobulin A nephropathy: clinical remission rate, steroid sparing effect, and maintenance of renal function

Abstract: BackgroundThe long-term prognosis of immunoglobulin A nephropathy (IgAN) is reportedly poor. In Japan, tonsillectomy-steroid pulse therapy has frequently been used for treatment of early IgAN, with favorable outcomes. However, steroid usage is sometimes limited due to adverse reactions. To reduce the total dose of steroids, we have been using mizoribine (MZR) in combination with tonsillectomy-steroid pulse therapy since 2004. Here we report a retrospective evaluation of our protocol outcome.MethodsForty-two pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Moreover, previous basic science studies have suggested that MZR regulates the glucocorticoid receptor function and might enhance the efficacy of corticosteroids [8]. Actually, a previous clinical study reported that the use of MZR for the treatment of nephrotic syndrome [9] and immunoglobulin A nephropathy [10]. These drug profiles indicate that MZR could be useful and safe as a treatment for TTP.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, previous basic science studies have suggested that MZR regulates the glucocorticoid receptor function and might enhance the efficacy of corticosteroids [8]. Actually, a previous clinical study reported that the use of MZR for the treatment of nephrotic syndrome [9] and immunoglobulin A nephropathy [10]. These drug profiles indicate that MZR could be useful and safe as a treatment for TTP.…”
Section: Discussionmentioning
confidence: 97%
“…Historically, mizoribine has been used to suppress rejection reactions in kidney transplantation [ 20 , 21 ], lupus nephritis [ 22 , 23 ] and rheumatoid arthritis. Mizoribine has also been reported to be effective as a treatment for IgA nephropathy [ 24 , 25 ]. It is approved as a treatment of NS in Japan [ 3 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the pathological diagnosis was IgAN with few active lesions, although the lesions were predominantly chronic. We previously reported that the use of steroid pulse therapy in combination with MZR following tonsillectomy is effective in improving urinary findings and preserving the renal function when treating IgA nephropathy in patients with renal impairment (6,7).…”
Section: Discussionmentioning
confidence: 99%